Perencanaan Ulang Jembatan Kalibanger Integrasi BIM 4D - Syifa Pradita; Bambang Setiabudi; Asri Nurdiana (Jurnal Sipil dan Arsitektur, 2024)
Technological developments in the construction world are also growing along with technology development. The application of BIM (Building Information Modeling) is one of the technological developments that can simplify the construction process, optimize time and human resources, and collaboration between stakeholders. Kalibanger Bridge is one of the bridges that crosses the Kalibanger River, connecting Semarang City and Demak Regency. The Kalibanger Bridge Replacement Project has been carried out from September 2022 to October 2023. Based on BIM, the re-planning of Kalibanger Bridge, Semarang City, was done by re-planning, modeling, and project scheduling. The methods presented are data collection, data analysis and structural analysis, 3D modeling using Tekla Structures, preparation of RAB, and scheduling. The re-planning of Kalibanger Bridge with BIM integration is expected to increase the ease and accuracy of the quantity take-off process and facilitate the scheduling process.